Book of abstracts of the ICIEOM-CIO-IIIE International Conference 2015 - Amorim, Marlene Paula Castro (2015)
BOOK OF ABSTRACTS OF THE ICIEOM-CIO-IIIE INTERNATIONAL CONFERENCE 2015: ENGINEERING SYSTEMS AND NETWORKS: The way ahead for industrial engineering and operations management